Creative Reconstruction: A Systematic Approach to Reinventing Large Cities in Democratic Republic of Congo (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2015)
The current state of large cities in Democratic Republic of Congo highlights the necessity of reinventing cities. More than fifty years after the independence, these major cities, like Kinshasa the capital city, are in a state of are in a state of disrepair. They are damaged, dysfunctional, and more vulnerable. Today, these legacy cities do not meet the international requirements of livable cities. Democratic Republic of Congo faces the challenge of rebuilding its cities for sustainability. The movement for independence of African countries enabled the shift from colonial cities to legacy cities. It is important to understand the cultural and ideological foundations of colonial city. Commonly, colonial cities served as purpose-built settlements for the extraction and transport of mineral resources toward Europe. What's required is a creative reconstruction to achieve a desired successful urban change. Creative reconstruction tends to ensure urban transformation in relation with urbanization, by making continuous and healthy communities. Creative reconstruction seems appropriate way of building back cities in harmony with cultural values. The article provides a framework for urban regeneration. The study is based on principle of thinking globally and acting locally in building back better cities.